Implications of the kinematical structure of circumnuclear star-forming regions on their derived properties - Hägele, Guillermo Federico (2013)
We reviewthe results of high-dispersion spectroscopy of 17 circumnuclear star-forming regions (CNSFRs) in 3 nearby early spiral galaxies, NGC 2903, NGC 3310 and NGC 3351. We findthat single-Gaussian fitting to the Hβ and [O III]λ5007 Å line profiles results in velocity dispersions around 32 and 52 km s-1, respectively, while the IR Ca II triplet cross-correlation technique provides stellar velocity dispersion values close to 50 km s-1. Even though multiple kinematical components are present, the relation between gas velocity dispersion and Balmer emission line luminosity (L-σ relation) reproduces the correlation for disc giant HII regions albeit with a larger scatter. The scatter in the L-σ relation is considerably reduced when theoretical evolutionary corrections are applied suggesting that an age range is present in the sample of CNSFRs. To analyse the observed complex profiles, we performed multiple Gaussian component fits to the Hβ and [O III]λ5007 Å lines obtaining optimal fits with two Gaussians of different widths. These best fits indicate that the narrower component has average velocity dispersion close to 23 km s-1 while the broader component shows average values in the range 50-60 km s-1 for both lines, close to the observed stellar velocity dispersions. The fluxes of the broad and narrow Hβ components are similar. This is not the case for [O III]λ5007 Å for which the broad components have higher fluxes than the narrow ones, thus producing a clear segregation in their [OIII]/Hβ ratios. We suggest a possible scenario for understanding the behaviour of CNSFRs in the L-σ and σgas-σ* diagrams involving aninner gaseous disc responsible for the narrow component of the emission lines. Our main conclusion is that the presence of different kinematical components with similar total fluxes in the emission line spectrum of CNSFRs raises important doubts regarding the properties of the ionized gas derived from global line ratios obtained with low-resolution spectroscopy in star-forming regions in the central regions of early-type galaxies. Given the ubiquity of these star-forming systems, ionized gas analyses should be done preferably from high-dispersion spectra with high spatial resolution.